Food, not friend: Tadpoles of the sandpaper frog (Lechriodus fletcheri) cannibalise conspecific eggs as a food resource in ephemeral pools. (29th November 2019) - Gould, John; Clulow, John; Clulow, Simon
Abstract: Among the Amphibia, cannibalism is most commonly associated with tadpole species that exploit ephemeral systems. This behaviour may confer significant fitness benefits to those that cannibalise, given that these systems generally possess limited food resources, but will incur significant fitness costs to the cannibalised. Herein, we describe cannibalism of recently oviposited eggs of the sandpaper frog ( Lechriodus fletcheri ) by conspecific tadpoles as a likely adaptation to limited nutrient availability within highly ephemeral pools in which it is an obligate breeder. Field observations revealed L. fletcheri tadpoles actively preyed on conspecific eggs of recently oviposited spawn bodies, which were commonly consumed whole. When tadpoles were exposed to spawn for the first time in laboratory trials, they quickly engaged in extended periods of consumption, gorging themselves until they appeared to be full. We found this behaviour to be common in the field and suggest that conspecific eggs form a significant food resource for tadpoles of this species in the otherwise nutrient‐poor systems in which they breed. This feeding strategy might be common among anurans exploiting temporary aquatic systems that are nutrient‐poor and gives rise to many questions surrounding how individuals can utilise cannibalism to increase their fitness while simultaneously avoiding becoming victims of this behaviour themselves. Abstract : Field observations have revealed that L. fletcheri tadpoles actively prey on conspecific eggs of recently oviposited spawn, commonly consuming entire eggs whole. When tadpoles are exposed to spawn for the first time in the laboratory, they quickly engage in extended periods of consumption, gorging themselves. We show that this behaviour in common in the field, suggesting that conspecific eggs form a significant food resource for tadpoles of this species in the otherwise nutrient‐poor systems in which they develop.